Analysis of Income and Welfare Level of Rubber Farmers in Ujung Tanjung Village, Banyuasin Iii District, Banyuasin Regency - Purbiyanti, Erni; Sihombing, Andi Maikel; Sulastri, Merna Ayu (Akademi Komunitas Perkebunan Yogyakarta, 2024)
Rubber is a plantation commodity that has a very important role in Indonesia. Rubber plants are widespread throughout Indonesia, especially on the island of Sumatra, and also on other islands. This research was conducted in Ujung Tanjung Village, Banyuasin III District, Banyuasin Regency. The objectives of this study were (1) to calculate the cost and income of rubber farming. (2) to analyzing the welfare level of rubber farmers using welfare indicators according to the Central Statistics Agency. The research method used in this study is the survey method. The sampling method used is proportional stratified random sampling. The data used in this study consisted of primary data and secondary data. Data collection was carried out in December 2022 until it was completed. The conclusions of this study are (1) The income of rubber farming farmers in Ujung Tanjung Village obtained an average income of. IDR 35,694,800.22/lg/year or equal to IDR 2,970,816.69/lg/month. (2) Rubber farmers in Ujung Tanjung Village have a low welfare level of 9.37% and rubber farmers have a moderate level of farmer welfare of 50.00% while rubber farmers have a high level of farmer welfare of 40.63% of all farmer respondents rubber in the village of Ujung tanjung. (3) The strategy for developing rubber farming in Ujung Tanjung Village is in quadrant I supporting aggressive strategies, these strategies are utilizing available resources to meet demand, increasing production by utilizing fertilizer assistance from the government, and increasing cultivation land with available land to increase production.